KARDIOCHIRURGIA DOROSŁYCHAssessment of long-term results of the efficiency and blood supply of the upper limb after harvesting the radial artery as material for coronary artery bypass grafting - Kowalczyk, Piotr; Knap, Oktawian; Kempińska, Agnieszka; Parafiniuk, Mirosław; Mokrzycki, Krzysztof; Listewnik, Mariusz; Brykczyński, Mirosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Background: Despite progress in the treatment of IHD, the patients’ vessels are still used as the material for CABG, usually the saphenous vein, mammary or radial artery (RA). Aim: The aim of this study was to evaluate the influence of RA harvesting on the efficiency forearm blood supply. Material and Methods: The study was carried out on a group of 58 patients of both sexes, at mean age 55, operated on a mean of 5.6 years before the examination. A physical examination was carried out on the group of patients and a questionnaire concerning the quality of life was administered. Dynamic thermographic examination was performed in which the cold provocation test was employed and finally, dynamometric examination estimated exercise ability. Results: There were neither trophic changes nor any form of muscular atrophy. Responding to the questionnaire, 72.5% of patients did not have any complaints concerning the operated forearm, while 18.9% stated their complaints as insignificant. Five of the patients said that they experienced discomfort, which did not influence the functioning of their hand. Dynamometric examinations carried out did not reveal significant asymmetry between both limbs, as well as thermographic procedure, which showed almost the same pattern of heating curve of operated and non-operated extremity. Conclusions: The expression of pathological changes connected with RA harvesting in long-term observation reveals no contraindications for the harvesting of the vessel for CABG material. Preoperative negative Allen’s test is a good prognostic tool of efficiency of collateral upper limb blood supply after RA harvesting